2013
DOI: 10.1159/000343258
|View full text |Cite
|
Sign up to set email alerts
|

Using Neurobiological Measures to Predict and Assess Treatment Outcome of Psychotherapy in Posttraumatic Stress Disorder: Systematic Review

Abstract: Background: Trauma-focused cognitive-behavioral therapy (TF-CBT) and eye movement desensitization and reprocessing (EMDR) are effective treatments for posttraumatic stress disorder. However, little is known about their neurobiological effects. The usefulness of neurobiological measures to predict the treatment outcome of psychotherapy also has yet to be determined. Methods: Systematic review of randomized controlled trials (RCTs) focused on neurobiological treatment effects of TF-CBT or EMDR and trials with ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 108 publications
0
24
0
Order By: Relevance
“…Gonçalves et al (2011) investigated potential CBT biomarkers of efficacy in the treatment of PTSD and found results consistent with this meta-analysis regarding heart rate. In a recent systematic review (Zantvoord et al, 2013), also in patients with PTSD, reduced physiological reactivity was found in line with the decrease in symptoms after treatment with CBT. It is known that heart rate is increased in PTSD patients (but see exceptions below) in a wide variety of methodologies, including resting baseline studies, startle studies, standardized trauma cue studies, and idiographic trauma cue studies (Pole, 2007).…”
Section: General Resultsmentioning
confidence: 59%
“…Gonçalves et al (2011) investigated potential CBT biomarkers of efficacy in the treatment of PTSD and found results consistent with this meta-analysis regarding heart rate. In a recent systematic review (Zantvoord et al, 2013), also in patients with PTSD, reduced physiological reactivity was found in line with the decrease in symptoms after treatment with CBT. It is known that heart rate is increased in PTSD patients (but see exceptions below) in a wide variety of methodologies, including resting baseline studies, startle studies, standardized trauma cue studies, and idiographic trauma cue studies (Pole, 2007).…”
Section: General Resultsmentioning
confidence: 59%
“…The change in the brain function was analyzed before and after PDT, and the results of the control and pharmacotherapy groups were compared. [101] However, the difference in the methodologies of the studies makes their comparison difficult. For example, Buchheim suggested that PDT was very effective in patients with subgenual ACC overactive depression [100], whereas CBT did not show any relevance.…”
Section: Pdt (Psychodynamicpsychotherapy) and Depressionmentioning
confidence: 99%
“…A few studies have focused on endocrinological changes; however, results remain inconsistent and both an increase in cortisol and DHEA [31] as well as a decrease in cortisol [32] has been found after psychotherapeutic treatment. Additionally, a systematic review demonstrated a decrease in heart rate and blood pressure as well as changes in the activity of frontal brain structures and the amygdala through trauma-focused treatment [33]. Nevertheless, nothing is known about how psychotherapy changes altered levels of catecholamines and cytokines or DNA damage and DNA repair in PTSD.…”
mentioning
confidence: 99%